Identification of Plasmodium spp. in Neotropical primates of Maranhense Amazon in Northeast Brazil - Figueiredo, Mayra Araguaia Pereira [UNESP]; Di Santi, Silvia Maria; Manrique, Wilson Gómez; André, Marcos Rogério [UNESP]; Machado, Rosangela Zacarias [UNESP] (Public Library of Science (PLoS), 2017)
In the Brazilian Amazon region, malaria caused by Plasmodium malariae is considered to be a zoonosis because of cross-transfer of the parasite between humans and Neotropical primates. To contribute information on this issue, we investigated occurrences of natural infection with Plasmodium sp. among Neotropical primates in the Maranhense Amazon (Amazon region of the state of Maranhão), in the northeastern region of Brazil. Blood samples were collected from 161 Neotropical primates of six species that were caught in an environmental reserve (Sítio Aguahy) and from captive primates (CETAS—Wildlife Screening Center, municipality of São Luís), in Maranhão. Plasmodium sp. was diagnosed based on light microscopy, PCR, qPCR and LAMP for amplification of the 18S rRNA gene. Serum samples were also assayed by means of indirect immunofluorescence for IgG antibodies against P. malariae/P. brasilianum, P. falciparum and P. berghei. Parasites were detected through light microscopy on five slides from captive primates (four Sapajus spp. and one Callithrix jacchus). In the molecular tests, 34.16% (55/161) and 29.81% (48/161) of the animals sampled were positive in the qPCR and PCR assays, respectively. In the PCR, 47/48 animals were positive for P. malariae/P. brasilianum; of these, eight were free-living primates and 39 from CETAS, São Luís. One sample showed a band in the genus-specific reaction, but not in the second PCR reaction. Anti-P. malariae/P. brasilianum IgG antibodies were detected in four serum samples from Sapajus spp. in captivity. In this study, circulation of P. malariae/P. brasilianum in Neotropical primates was confirmed, with low levels of parasitemia and low levels of antibodies. The importance of these animals as reservoirs of human malaria in the region studied is still unknown. This scenario has an impact on control and elimination of malaria in this region.